1950
DOI: 10.3181/00379727-73-17619
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tolerance of Mice to Lethal X-Radiation as a Result of Previous Sublethal Exposures.

Abstract: INCREASED RESISTANCE TO RADIATIONutilized for the synthesis of non-essential amino acids by the intact young rat, The possi'bility that urea can !be utilized in anabolic processes in the eviscerate rat should be considered.The possibility that urea can be metabolized in the eviscerate rat weakens one point of evidence that urea synthesis occurs only in the liver. The earlier studies( 1) on nlephrectomized-hepatectomized animals have shown that the blood and tissue urea did not change during the times that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1959
1959
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A number of studies have demonstrated adaptive response at the whole-animal level in vertebrates. Some of the documented positive effects of pre-irradiation have included: reduced short-term mortality rates in mice, [1][2][3][4] reduced frequency of chromosome abnormalities in mice 5,6 and humans [7][8][9] , and reduced risk of cancer development in mice. [10][11][12] These studies provide clear evidence for reduction and/or delay of genetic instability and ultimately disease through adaptive response; however, the majority of both in vivo and in vitro studies have focused on somatic markers of DNA damage or cancer.…”
Section: Heritable Mutationsmentioning
confidence: 99%
“…A number of studies have demonstrated adaptive response at the whole-animal level in vertebrates. Some of the documented positive effects of pre-irradiation have included: reduced short-term mortality rates in mice, [1][2][3][4] reduced frequency of chromosome abnormalities in mice 5,6 and humans [7][8][9] , and reduced risk of cancer development in mice. [10][11][12] These studies provide clear evidence for reduction and/or delay of genetic instability and ultimately disease through adaptive response; however, the majority of both in vivo and in vitro studies have focused on somatic markers of DNA damage or cancer.…”
Section: Heritable Mutationsmentioning
confidence: 99%
“…At that time he irradiated groups of mice using beta radiation and observed a "recovery from the radiation damage" when the conditioning sublethal dose was applied prior to the test lethal dose. Raper's experiments were repeated a few years later and showed the same effect but no detailed explanation was proposed (Cronkite et al 1950). Next, in the late 1950s, the historical Elkind-Sutton experiments were conducted (Elkind and Sutton 1959).…”
Section: Discussionmentioning
confidence: 99%
“…1, where the difference between the D 1 + D 2 scheme (with time Δt between doses) and the single D 2 one is denoted as delta (δ) parameter, which is the main quantification of the generalized Yonezawa effect. One has to note, however, that the first observation of this effect (without deeper explanation) was conducted by Prof. Raper in 1940s during the Manhattan Project (Raper 1947;Cronkite et al 1950).…”
Section: Introductionmentioning
confidence: 99%
“…Cronkite et coll. [33] observent un « surrecouvrement », c'est-à-dire une radio-résistance. Plus récem ment, Nachtwey, Ainsworth, Leong [26] observent sur le porc un recouvre ment de 51 % au 3e jour, de 65 % au 7e jour; la radio-résistance apparaît au 20e jour où la DL 50 est de 164 % par rapport à la DL 50 résultant d'une dose unique.…”
Section: Ebr Des Protons De 3 Gev Sur Le Rat 8lunclassified